Community-based initiatives and structural barriers: Examples from various communities of refugee backgrounds - Hà, Thị Ân (2023)
People of refugee backgrounds are often imposed as a burden for a host society while those people actually bring diverse expertise, knowledge and contribution to communities where they resettle. They have their own strengths and resilience and at the same time they have faced challenges and difficulties during the resettlement process. This study aims to explore how community of refugee backgrounds utilized their strengths to develop initiatives for responding to adversities and improving their well-being. Using qualitative research method and ethographic approach, the author worked with five communities from various refugee backgrounds and five refugee service agencies through in-depth, semi-structured interviews, focus groups, and observations. The findings demonstrate the importance and power of community-driven programs and community level interventions among communities of refugee backgrounds in resettlement. Structural barriers such as gaps between clinical social work and macro social work, funding and market driven approach, and homogeneous mindsets about refugee populations are also found. This research raises attentions on the existing problems of Western social work education and practice. That are the ignoring values of community-centered and the prioritizing individual-centered programs or gaps between clinical social work and macro social work. Changes are needed. As conclusion, it is suggested for more awareness and appreciation of community participation, community-based programs, and interventions at community level in both education and practice.